Review on user authentication on mobile devices - Abdul Gimba, Usman; Mohd Ariffin, Noor Afiza (Semarak Ilmu Publishing, 2024)
Mobile devices have made life easier and provide great convenience in the 21st century. They give users the freedom to gain access anytime, anywhere to numerous applications with the help of information and communication technology. Online shopping, social media, and banking transactions, to name a few, are all now at our fingertips. However, they also come at a cost, as black/grey hat hackers attempt to gain access to these devices. They tend to access sensitive information on these devices by unlocking them, and, moreover, some applications and mobile services are exposed to security threats. This paper reviews the current existing authentication methods on mobile devices, which are based on knowledge and biometrics and are used for authentication. The types of authentication factors, including Single Factor, Two-Factor, and Multifactor authentication, are also discussed, along with the associated threats. The paper points out that the most secure authentication factors, and multifactor authentication is the current trend in mobile authentication.